IDENTIFIKASI MODAL KELUARGA PADA 3 UKM DI BANDUNG - Budiana Gomulia; Elvy Maria Manurung (Bina Ekonomi, 2014)
It is factual that the establishment of an SME generally starts with the family members or at least with the indirect support and family assistance. This study is focused on finding the role of capital provided by the family at the time of establishing and developing SME, either in the form of money capital and financial assets or in the form of values, or emotions-time-care. The research is performed with using qualitative methods, namely Multi Case Studies on three SMEs in Bandung which are selected as the research object. Results from recorded interview are coded according to the research theme. Pierre Bourdieu’s theory of capital is used to analyze and to explore meaning from the findings. The findings show that economic capital is not the only factor that plays a role in starting and developing businesses in the three cases. There are other capitals such as cultural capital and social capital. Symbolic capital can be built in line with the cultural and social capital accumulated along the life of the business.